THE STUDY OF IMMUNOMODULATING PROPERTIES OF THE VITANAM - V. S. Orlova; E. V. Orlova; A. S. Timokhina; Ya. M. Stanishevskiy (Разработка и регистрация лекарственных средств, 2019)
In the present paper some immunological effects on T- and B-cell immunity of a new drug Vitanam - selective activator of Ca-dependent NO-synthase were shown on the animal model.